2006
DOI: 10.1002/jor.20196
|View full text |Cite
|
Sign up to set email alerts
|

The autotomy relief effect of a silicone tube covering the proximal nerve stump

Abstract: A technique of covering the proximal nerve stump (PNS) has been reported as a preventative method or treatment for neuroma. However, its detailed pain relief mechanism remains unknown. We created a silicone tube model in which the PNS of the rat sciatic nerve was introduced into the tube, whereas the controls had no tube. The score of autotomy observed in the tube group was lower than that in the control group at 3 days to 2 weeks after surgery, which suggested that the silicone tube had pain-like behavior inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 56 publications
1
33
0
1
Order By: Relevance
“…However, the exact role of mast cells in nerve regeneration is still controversial. Okuda et al34 attributed the decrease of neuropathic pain to reduction in mast cells accumulation in regenerating nerves. This is in opposition to other researches who found that mast cells accumulation during neural elongation not only does not elicit any pain symptoms but even stimulates the nerve regeneration 26, 35, 36…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact role of mast cells in nerve regeneration is still controversial. Okuda et al34 attributed the decrease of neuropathic pain to reduction in mast cells accumulation in regenerating nerves. This is in opposition to other researches who found that mast cells accumulation during neural elongation not only does not elicit any pain symptoms but even stimulates the nerve regeneration 26, 35, 36…”
Section: Discussionmentioning
confidence: 99%
“…However, the onset of autotomy as well as average autotomy index in both groups did not differ significantly. We believe that inflammatory cells derived cytokines, such as tumor necrosis factor‐b (TNF‐β) or transforming growth factor‐b1 (TGF‐β1), may play a role in the generation of neuropathic pain in the chitosan group, despite absence of neuromas 3, 34…”
Section: Discussionmentioning
confidence: 99%
“…Morphological analysis is the most commonly used method, usually performed in light, 18,22,24,26,27,29,45,46,32,34,50,36,38,43,44,49,19,20,47,39,49 electron, 10,30,32,50,36,40 fluorescence 19,37,38,40 or confocal laser microscopy. 20,43,44 Data on the level where biopsies of the nerve and the neuroma are taken and analysed are heterogeneous and often missing, preventing appropriate comparison of results: Chim et al 16 Haematoxylin and eosin 16,18e20,36,50,37,40,49 and toluidine blue 10,18,22,32,45,46,24,19,25,27,30,38,43,…”
Section: Evaluation Methods Histologymentioning
confidence: 99%
“…20,43,44 Data on the level where biopsies of the nerve and the neuroma are taken and analysed are heterogeneous and often missing, preventing appropriate comparison of results: Chim et al 16 Haematoxylin and eosin 16,18e20,36,50,37,40,49 and toluidine blue 10,18,22,32,45,46,24,19,25,27,30,38,43,44 are the most commonly used stains; some studies also use Masson's thricome, 10,20,37 which also allows the labelling of the connective tissue. 70 This is sometimes combined with immunolabelling, the most common targets being S100 protein, 16,25e27,43 neurofilament 200 (NF200), 10,25,30,37,38 neuronal growthassociated protein (GAP)-43, 20,24,43,44 macrophages (ED-1), 20,27,28,43 nerve growth factor (NGF) 27 and calcitonin gene-related peptide (CGRP). 24,28,30 Double staining has also been reported to identify axons of different origin.…”
Section: Evaluation Methods Histologymentioning
confidence: 99%
See 1 more Smart Citation